Selling Price of Acacia Log Analysis by Approaching The Production Cost of Plantation Forest - Refdanil Nurcan; Evi Sribudiani; Sudarmalik ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The low of price Acacia log is caused by coorperative operation betweenplantation forest with forest product industry in implementation on PermenhutP.29/2012. The aims of the study were to know: determinant factors and costproduction of Acacia mangium and Acacia crassicarpa plantation forest, the priceof A. mangium and A. crassicarpa log based by cost production, and the financialanalysis of plantation forest used the price log based on production cost ofplantation forest and actual price of log Acacia. Reasearch is conducted in AraraAbadi Company in Distric of Rasau Kuning and Pusaka. Data analysis is usedproduction cost of plantation forest at 3th and 4th rotation are land clearing,seedling, planting, weeding, harvesting, tansporting and potential stands. This dataused to find the price of Acacia log in industry. The actual price of Acacia inmarket was got from interview. Data analysis used the financial analysis byparameters Net Present Value, Benefit Cost Ratio, and Internal Rate of Return.The assumtion of study used interest rate (15%) and plantation forest bussines (5years). The result of study showed that the determinant factors are purchasementof seed, land potential, salary of planting, salary of over cultivate take, salary ofwood cut and cost carry to pile place of log and salary of cultivate KCa. Theproduction cost and the log price of A. crassicarpa plantation forest is higher thanA. mangium. The plantation forest is financially feasible but happenned todecrease to the next rotation.Keywords: plantation forest, analysis financial, Acacia mangium,Acacia crassicarpa